Aktivitas dan Stabilitas Fisik Lotion Tabir Surya dari Ekstrak Daun Rambai - Warnida, Husnul; Nurhasnawati, Henny; Sukawaty, Yullia; Ardhita, Ardhita (FASKES : Jurnal Farmasi, Kesehatan, dan Sains, 2025)
Background: Long-term, intense sun exposure can cause erythema and sunburn, as well as premature aging and skin cancer. For generations, the people of the Banjar tribe of Borneo have applied a wet paste of Sonneratia caseolaris leaves mixture on the skin when undertaking tasks in the hot sun. The Sonneratia caseolaris tree is a mangrove plant that grows on river banks throughout the Borneo Island. Objectives: The study aims to formulate Sonneratia caseolaris leaves ethanol extract into a stable lotion and test its efficacy as a sunscreen. Methods: Sonneratia caseolaris leaves were macerate with 70% ethanol, and the sunscreen activity of the extract was examined in vitro with a UV-visible spectrophotometer, and then formulated into a lotion dosage form. Organoleptic and homogeneity observations, pH measurements, viscosity measurements, and spreadability measurements were all performed on the lotion. Following that, the lotion sunscreen activity of was tested in vitro. Results: The Sonneratia caseolaris extract sunscreen lotion has met the requirements of organoleptic, homogeneity, pH, viscosity, and spreadability tests. Conclusions and suggestions: Sunscreen lotion with 2.5% Sonnerata caseolaris extract classified as standard suntan. Sonneratia caseolaris extract of Borneo has the potential to develop as a raw material for herbal cosmetics.